AI-DRIVEN PRINT ADVERTISING IN EDUCATIONAL INSTITUTIONS - deshmukh, Nikhil Kakade; Mahadik, Ramchandra Vasant; Ojha, Varun; Kaushik, Vaibhav; Murthy, G.T.Harikrishna; Rakash, Om (ShodhKosh: Journal of Visual and Performing Arts, 2025)
The use of Artificial Intelligence (AI) in the print advertisement is an extreme step in the landscape of the educational system in which the educational institution is keen to enhance their reach, communication, and branding abilities. The traditional application of print ad, which was once said to be the one-size-fits-all ad with no dynamism, is becoming a dynamic application where the idea of AI-controlled data is applied and automated. This paper explores the application of AI technologies to automatize the print campaigns of educational industry, such as predictive analytics, machine learning, and augmented reality (AR). It investigates how the AI assists institutions in locating the target audiences more precisely, tailor the content, and improve the result of the campaign with the assistance of the data-driven feedback systems. The introduction of such features as QR codes, AR games and AI-made design patterns helps print media to cross its traditional boundaries and establish an interactive and measurable communication. The study is a mixed-method strategy that balances both quantitative data of institutional campaigns and qualitative data of the marketing professionals. The results indicate that AI-enhanced print advertising does not only help in raising student engagement and enrollment rates but also, institutional branding through the integration of traditional and digital media platforms. The suggested theoretical framework is built on the basis of the Technology Acceptance Model and Diffusion of Innovations theory that presented the interdependence between the technological adoption, user perception and the marketing results.